2006
DOI: 10.1007/s10995-005-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Policies and Practices Related to Breastfeeding in Massachusetts: Hospital Implementation of the Ten Steps to Successful Breastfeeding1

Abstract: Rates of self-reported implementation of the Ten Steps are relatively high in Massachusetts. Step 1 implementation is significantly associated with formula availability, and overall implementation with acceptance of free formula. Continued assessment is needed to confirm these results in larger samples and to examine the relationship of implementation of individual steps, breastfeeding rates, and health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Based on UNICEF report (2006) infant and mother skin to skin contact in first hour of life is one of ten steps in breastfeeding success [34]. It has been reported that skin to skin contact is an effective intervention to promote babies' sucking ability, weight gain, body temperature stability and mother's satisfaction [35].…”
Section: Discussionmentioning
confidence: 99%
“…Based on UNICEF report (2006) infant and mother skin to skin contact in first hour of life is one of ten steps in breastfeeding success [34]. It has been reported that skin to skin contact is an effective intervention to promote babies' sucking ability, weight gain, body temperature stability and mother's satisfaction [35].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) (2002,2011) recommends exclusive breastfeeding for 6 months, to be continued as an accompaniment to food for 2 years or more, advice which has long been integral to breastfeeding promotion in the UK and international antenatal and postnatal programmes (Malik and Cutting, 1998;UNICEF UK, 2002;Dykes, 2003;Department of Health (DH), 2004. The same recommendations are made in the US (Grizzard et al, 2006) and Australia (Blyth et al, 2002). Educational interventions designed to promote breastfeeding target women especially in the lower socio-economic bracket, who are found to be significantly less likely to initiate or sustain breastfeeding (Mahon-Daly and Andrews, 2002).…”
Section: Researchmentioning
confidence: 90%
“…Reluctance to "push" breastfeeding (concerned about making mothers feel guilty about their personal feeding choices) 16,29,46,58,75,77,81 Traditional beliefs that prioritize maternal rest over infant feeding (eg, belief that a mother is ill immediately postbirth and should not be made to room-in) 60 Staff approach that is flexible, open, and embodied is viewed by patients as more effective than rigid, rules-driven approach to breastfeeding support 81 Reframing language used with new mothers to be more breastfeeding friendly 64 Staff support for and encouragement of BFI policies in the NICU 71 Restricting staff access to pacifiers or formula for supplementation 30,35,46,56 Access to human donor milk/milk banks 57,83 Establish cup feeding of expressed breast milk instead of nipple feeding as standard practice in NICU (with use of formula feeding where indicated) 28 Family support and other resources Lack of family support to breastfeed 73 Family members offer supplements, prelacteal feeds 29 Financial barriers for mothers wishing to obtain breast pumps 69,78 Mothers' involvement with breastfeeding peer support programs (mother-tomother support) 36 …”
Section: Infrastructure and Routinesmentioning
confidence: 99%